Lifting the limits on high speed wireless data access using antennaarrays. - Lozano, A.
The explosive growth of both the wireless industry and the Internet is creating a huge market opportunity for wireless data access. Limited Internet access, at very low speeds, is already available as an enhancement to some existing cellular systems. However, those systems were designed with the purpose of providing voice services and-at most-short messaging, but not fast data transfers. In fact, as shown in this article, traditional wireless technologies are not very well suited to meet the demanding requirements of providing very high data rates with the ubiquity, mobility, and portability characteristic of cellular systems. Increased use of antenna arrays appears to be the only means of enabling the types of data rates and capacities needed for wireless Internet and multimedia services. While the deployment of base station arrays is becoming universal, it is really the simultaneous deployment of base station and terminal arrays that can unleash unprecedented levels of performance by opening up multiple spatial signaling dimensions
Keywords: Internet; Antenna arrays; Base station arrays; Cellular systems; High data rates; High speed wireless data access; Multiple spatial signaling; Receive arrays; Short messaging; Terminal arrays; Transmit arrays; Voice services; Wireless Internet services; Wireless industry; Wireless multimedia services; Wireless technologies